Four sesquiterpene glycosides from loquat (Eriobotrya japonica) leaf ameliorates palmitic acid-induced insulin resistance and lipid accumulation in HepG2 Cells via AMPK signaling pathway - Li,Jiawei; Ding,Xiaoqin; Jian,Tunyu; Lü,Han; Zhao,Lei; Li,Jing; Liu,Yan; Ren,Bingru; Chen,Jian (PeerJ, 2020)
Insulin resistance (IR), caused by impaired insulin signal and decreased insulin sensitivity, is generally responsible for the pathophysiology of type 2 diabetes mellitus (T2DM). Sesquiterpene glycosides (SGs), the exclusive natural products from loquat leaf, have been regarded as potential lead compounds owing to their high efficacy in hypoglycemia and hypolipidemia. Here, we evaluated the beneficial effects of four single SGs isolated from loquat leaf, including SG1, SG2, SG3 and one novel compound SG4 against palmitic acid-induced insulin resistance in HepG2 cells. SG1, SG3 and SG4 could significantly enhance glucose uptake of insulin-resistant HepG2 cells at non-cytotoxic concentration. Meanwhile, Oil Red O staining showed the decrease of both total cholesterol and triglyceride content, suggesting the amelioration of lipid accumulation by SGs in insulin-resistant HepG2 cells. Further investigations found that the expression levels of phosphorylated AMPK, ACC, IRS-1, and Akt were significantly up-regulated after SGs treatment, on the contrary, the expression levels of SREBP-1 and FAS were significantly down-regulated. Notably, AMPK inhibitor Compound C (CC) blocked the regulative effects, while AMPK activator AICAR mimicked the effects of SGs in PA-treated insulin-resistant HepG2 cells. In conclusion, SGs (SG4>SG1≈SG3>SG2) improved lipid accumulation in insulin-resistant HepG2 cells through the AMPK signaling pathway.
Keywords: Loquat leaf; Sesquiterpene glycosides; Insulin resistance; HepG2 cells; AMPK